Fucoidan attenuates chronic colitis and behavioral deficits by reshaping gut microbiota-brain axis balance - Zi-Wei Ye; Zhong-Yu Yuan; Jun Wang; Hua Li; Cheng-Fu Li; Guang-Hui Xu; Li-Tao Yi; Wei-Feng Huang (Journal of Functional Foods, 2024)
Inflammatory bowel disease (IBD) often coexists with depression, posing considerable challenges for treatment. This study aimed to investigate the therapeutic potential of fucoidan, a compound derived from Laminaria japonica, in a dextran sulfate sodium (DSS)-induced model of IBD with comorbid depression. The administration of fucoidan demonstrated significant therapeutic efficacy, as it reduced disease activity, increased sucrose preference, and decreased immobility time, suggesting benefits for both IBD and depression. Fucoidan had a noteworthy impact on the gut microbiota, characterized by an increase in the abundance of Firmicutes and Lactobacillus. Additionally, it strengthened the integrity of the colonic barrier by upregulating tight junction proteins (ZO-1, Occludin, and Claudin-1) and reduced colonic inflammation via the TLR4/NF-κB pathway. Fucoidan also exhibited the ability to suppress peripheral inflammation and lower stress response hormone levels, particularly corticosterone. Furthermore, fucoidan reduced the number of microglia, as well as decreasing cytokines such as interleukin-1 beta (IL-1β) and tumor necrosis factor alpha (TNF-α) levels, indicating a decrease in neuroinflammation in IBD-afflicted mice. In conclusion, fucoidan effectively mitigates IBD comorbid with depression by modulating the gut microbiota-brain axis. These findings offer promise for fucoidan as a natural compound to manage both IBD and associated depressive symptoms.